N-acetyl cysteine restores the fertility of vitrified–warmed mouse oocytes derived through ultrasuperovulation - Mukunoki, Ayumi (PLoS One, 2019)
Oocyte cryopreservation is useful for preserving fertility and storing genetic resources. However, the small number of oocytes acquired using conventional treatment to induce superovulation and the reduction of fertility due to cryopreservation represent significant problems. Herein, we vitrified the oocytes derived through high-yield superovulation using inhibin antiserum and equine chorionic gonadotropin (IAS + eCG: IASe) and examined the yield of cryopreserved oocytes and survival rates relative to those of vitrified–warmed mouse oocytes derived through conventional superovulation using equine chorionic gonadotropin (eCG). Furthermore, we investigated the effects of N-acetyl cysteine on the fertility and developmental potential of vitrified–warmed oocytes derived using IASe. Compared with eCG, IASe increased the yield of cryopreserved oocytes and achieved equivalent survival rates. N-acetyl cysteine (0.5 mM) increased the fertilization rate of vitrified–warmed oocytes derived using IASe. Vitrification decreased thiol levels in the zona pellucida (ZP), while warming followed by N-acetyl cysteine treatment increased free thiol levels in ZP. Moreover, N-acetyl cysteine treatment recovered zona hardening by cleaving disulfide bonds and promoting the expansion of ZP. Two-cell embryos derived via in vitro fertilization using N-acetyl cysteine developed into normal pups through embryo transfer. Therefore, we developed an efficient technique for the production of cryopreserved oocytes using IASe through superovulation and found that N-acetyl cysteine improves the fertility of vitrified–warmed oocytes by cleaving the disulfide bonds and promoting the expansion of ZP.